Uncovering the cyber security challenges in healthcare. Issue 4 (April 2020) - Hockey, Alyn
Abstract : The now infamous WannaCry hack of May 2017 not only sent shockwaves through the healthcare industry in the UK, but also caused cyber security concerns to understandably balloon across all sectors. It made people sit up and question the extent to which large, household name organisations like the National Health Service were acting to protect the critical data held about individuals under their care.